Finding Solutions for Fibrosis: Understanding the Innate Mechanisms Used by Super‐Regenerator Vertebrates to Combat Scarring. Issue 15 (24th May 2021) - Durant, Fallon; Whited, Jessica L.
Abstract: Soft tissue fibrosis and cutaneous scarring represent massive clinical burdens to millions of patients per year and the therapeutic options available are currently quite limited. Despite what is known about the process of fibrosis in mammals, novel approaches for combating fibrosis and scarring are necessary. It is hypothesized that scarring has evolved as a solution to maximize healing speed to reduce fluid loss and infection. This hypothesis, however, is complicated by regenerative animals, which have arguably the most remarkable healing abilities and are capable of scar‐free healing. This review explores the differences observed between adult mammalian healing that typically results in fibrosis versus healing in regenerative animals that heal scarlessly. Each stage of wound healing is surveyed in depth from the perspective of many regenerative and fibrotic healers so as to identify the most important molecular and physiological variances along the way to disparate injury repair outcomes. Understanding how these powerful model systems accomplish the feat of scar‐free healing may provide critical therapeutic approaches to the treatment or prevention of fibrosis. Abstract : Fibrosis is a serious medical problem that remains unresolved in many cases. However, regenerative organisms have evolved to avoid fibrosis and are capable of scar‐free healing. Herein, the physiological and molecular mechanisms behind fibrosis and regenerative wound healing are reviewed and how this knowledge may be applied to solve issues in human health is explored.